Influence of Sliding Rate and Load with Friction on NiTi Shape Memory Alloy Wear Resistance - Avcil, Ali; Eker, Aysegul Akdogan; Kucukyildirim, Bedril Onur (SPRINGER, 2022)
The effect of load and sliding rate on wear resistance of a NiTi alloy in martensitic and austenitic conditions with dry friction by a ball-disk scheme is studied. Martensitic transformation temperature and wear mechanism are analyzed using differential calorimetry, scanning electron microscopy, and energy-dispersive spectrum analysis. It is shown that friction coefficient decreases by about 40% with increase in load, and sliding rate has a smaller and ambiguous effect on NiTi alloy friction characteristics. Austenitic phase exhibits a slower wear rate than martensitic phase with all of the friction regimes used.
Keywords: shape memory alloys; NiTi; wear resistance; friction coefficient; reverse martensitic transformation; TRIBOLOGICAL BEHAVIOR; EVOLUTION; SMA; Metallurgy & Metallurgical Engineering